HYBRID POWER PLANT FEASIBILITY STUDY IN MANDANGIN ISLAND USING HOMER SOFTWARE - Soeprapto Soeprapto; Unggul Wibawa; Mahfudz Shidiq (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2016)
In this research, a feasibility study of Diesel Power Plant (diesel) existing on the island Mandangin with hibrid using Renewable Energy (ET) in the form of photovoltaic (PV). HOMER is an optimization analysis software for power generation system design, seen from the value of the Net Present Cost (NPC) the lowest. HOMER itself is an abbreviation of Hybrid Optimization Model for Electric Renewable developed by the National Renewable Energy Laboratory (NREL) USA. The system design is based on data obtained from diesel Mandangin island. of the total power of 1500 kW able to be raised, but only used up to 400 kW. For design optimization was performed by adding a PV system as a source of renewable energy amounting to 300 kW. Analysis of the resulting HOMER, designs are made to meet the needs of 100% load with energy excess of 0.01%. Hybrid system configuration are made which have high initial costs, but the total NPC generated was reduced by 4,948,556. For the amount of fuel used, Hybrid system uses less fuel amount to a reduction of 184 565 L / year or a total of 180.931 per year compared with the existing diesel system. The amount of emissions released Hybrid system was also decreased with the decrease of 486.123 kg / yr of CO2 and 1,200 kg / yr of CO. In conclusion, HOMER is a software that can optimize power generation.